Bioconjugation of peptides using advanced nanomaterials to examine their interactions in 3D printed flow‐through device. Issue 3 (30th December 2015) - Michalek, Petr; Richtera, Lukas; Krejcova, Ludmila; Nejdl, Lukas; Kensova, Renata; Zitka, Jan; Kopel, Pavel; Heger, Zbynek; Adam, Vojtech; Kizek, Rene
Abstract : Peptide–peptide interactions are crucial in the living cell as they lead to the formation of the numerous types of complexes. In this study, synthetic peptides containing 11 of cysteines (α‐domain of metallothionein (MT)) and sialic acid binding region (130‐loop of hemagglutinin (HA)) were employed. The aim of the experiment was studying the interactions between MT and HA‐derived peptides. For this purpose, fragments were tagged with cysteines at C ‐terminal part to serve as ligand sites for PbS and CuS quantum dots (QDs), and therefore these conjugates can be traced and quantified during wide spectrum of methods. As a platform for interaction, γ‐Fe2 O3 paramagnetic particles modified with tetraethyl orthosilicate and (3‐aminopropyl)triethoxysilane (hydrodynamic diameter 30–40 nm) were utilized and MT/HA interactions were examined using multi‐instrumental approach including electrochemistry, electrophoretic methods, and MALDI‐TOF/TOF mass spectrometry. It was found that peptides enter mutual creation of complexes, which are based on some of nonbonded interactions. The higher willingness to interact was observed in MT‐derived peptides toward immobilized HA. Finally, we designed and manufactured flow‐through electrochemical 3D printed device (reservoir volume 150 μL) and utilized it for automated analysis of the HA/MT metal labels. Under the optimal conditions, (deposition time and flow rate 80 s and 1.6 mL/min for CuS and 120 s and 1.6 mL/min PbS, respectively), the results of peptide‐conjugated QDs were comparable with atomic absorption spectrometry.